2020
DOI: 10.1186/s40360-020-00424-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety in patients treated with teicoplanin with a target trough concentration of 20 μg/mL using a regimen of 12 mg/kg for five doses within the initial 3 days

Abstract: Background: A trough concentration (C min) ≥20 μg/mL of teicoplanin is recommended for the treatment of serious methicillin-resistant Staphylococcus aureus (MRSA) infections. However, sufficient clinical evidence to support the efficacy of this target C min has not been obtained. Even though the recommended high C min of teicoplanin was associated with better clinical outcome, reaching the target concentration is challenging. Methods: Pharmacokinetics and adverse events were evaluated in all eligible patients.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The results showed that CL of TEI in the CVVHDF mode was 5.8 ± 4.2 ml/h/kg, which was higher than that of CVVH and the CVVHD mode ( Bellmann et al, 2010 ). The size of the unbound TEI fraction and trough concentrations correlates inversely with the plasma albumin level ( Yano et al, 2007 ; Brink et al, 2015 ; Ueda et al, 2020 ). However, no studies have confirmed whether hypoalbuminemia enhanced hemofilter clearance.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that CL of TEI in the CVVHDF mode was 5.8 ± 4.2 ml/h/kg, which was higher than that of CVVH and the CVVHD mode ( Bellmann et al, 2010 ). The size of the unbound TEI fraction and trough concentrations correlates inversely with the plasma albumin level ( Yano et al, 2007 ; Brink et al, 2015 ; Ueda et al, 2020 ). However, no studies have confirmed whether hypoalbuminemia enhanced hemofilter clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Because the population is highly heterogeneous regarding the source of infection, we divided the patients into high/moderate and low-risk infections. High/moderate risk infections consisted of bloodstream infections and complicated infections (endocarditis, ventilator-associated pneumonia, osteomyelitis and arthritis infections, and central nervous system infections) [ 19 ]. Low-risk infections included skin and soft tissue infections, urinary tract infections, intra-abdominal infections, and cases of pneumonia with the exception of ventilator-associated pneumonia.…”
Section: Methodsmentioning
confidence: 99%
“…No association was reported between teicoplanin-induced nephrotoxicity and its trough concentrations [ 42 ]. Teicoplanin trough concentrations ≥20 mg/L compared with <20 mg/L showed no significant difference in the rate of adverse events in patients with MRSA infections [ 38 ]. Although no teicoplanin-induced renal impairment was reported in trough concentrations ≥10 mg/L, the hepatotoxicity rate was 10% [ 43 ].…”
Section: Resultsmentioning
confidence: 99%